9, 10-Bis(N-methylcarbazol-3-yl-vinyl-2)anthracene: High contrast piezofluoro-chromism and remarkably doping-improved electroluminescence performance. (February 2016) - Liu, Wei; Ying, Shian; Sun, Qikun; Qiu, Xu; Zhang, Haichang; Xue, Shanfeng; Yang, Wenjun
Abstract: This paper reported the synthesis, optical and electroluminescent properties of 9, 10-bis( N -methylcarbazol-3-yl-vinyl-2)anthracene (MCA ).MCA could be facilely prepared by the Wittig–Horner reaction of N -methyl-3-formylcarbazole and 9, 10-bis(diethoxyphosphorylmethyl)anthracene and exhibited strong aggregation-induced and crystallization-enhanced emission (AIE/CEE) effect. Simple mechanical force could changeMCA solid from initial green to final red emission, affording high contrast piezofluorochromism with large spectral shift of up to 90 nm. WhenMCA was used as the emissive material in light-emitting diodes, the doped devices showed remarkably improved electroluminescence (EL) performance whose EL efficiency was 8 times higher than that of the non-doped device. Moreover, the dopant concentrations did not affect significantly the fluorescence properties of doped films and EL performances of doped devices, demonstrating the potential advantage of AIE/CEE luminogens applicable for EL dopants. Graphical abstract: Highlights: A simple AIE dye 9, 10-bis( N -methylcarbazol-3-yl-vinyl-2)-anthracene was synthesized. The compound exhibited larger PFC shift under simple mechanical force. The compound exhibited remarkably doping-improved EL performance. The compound exhibited remarkably dopant concentration-independent EL performance.